Diagnostic Markers for Studying the Dynamics of Adolescent Creativity Development at Arts Integrated Lessons - Seheda, Natalia; Tereshchenko, Svitlana (Journal of History Culture and Art Research, 2020)
The article details the final part of S. Tereschenko’s dissertation research on the methods of developing creativity of adolescents using integrated art lessons. In this publication, the authors provide a description of the scientific understanding of the construction of a pedagogical experiment aimed at studying the dynamics of adolescent creativity development using art-integrated lessons. The study aimed to identify the structure of creativity of adolescents, determine the developmental potential of integrated art lessons, select experimental testing of a set of psychological and diagnostic techniques, and identify the level of formation of structural components of creative competence adapted to the specifics of integrated art lessons. The set of tasks included a practice-oriented analysis of the creativity of adolescents in secondary education. Well-known diagnostic methods were used to study human creativity and their adaptation to art lessons and features of adolescence. Statistical proof of the effectiveness of the diagnostic apparatus was used to identify the level of formation of adolescents’ creativity in integrated art lessons. The study found that adolescent creativity is defined as a personal ability for productive, creative, and original self-expression by means of art. The structure of adolescent creativity includes the following: associative-visual thinking, creative imagination, artistic observation, and artistic self-expression. We have developed the characteristics that demonstrate the levels of adolescent creativity in integrated music training.